Sensitive Time-Resolved Fluorescence Immunoassay for Quantitative Determination of Oxyfluorfen in Food and Environmental Samples - Sheng, En Ze; Tan, Yu Ting; Lu, Yu Xiao; Xiao, Yue; Li, Zhen Xi (Frontiers in Chemistry, 2021)
The direct and indirect competition time-resolved fluorescence immunoassay (dc-TRFIA, ic-TRFIA) were established by combining the autofluorescence properties of lanthanide europium (Eu) with the monoclonal antibody of oxyfluorfen. The purified Europium antibody was optimized and the conditions such as the working concentration of europium antibody, monoclonal antibody and working buffer were optimized. In the optimal condition, the IC50 of dc-TRFIA was 10.27 ng/mL, the lowest detection limit IC10 was 0.071 ng/mL, the detection range (IC10-IC90) was 0.071-1074.3 ng/mL, the detection range (IC10-IC90) and IC50 of ic-TRFIA was 0.024-504.6 ng/mL, 2.76 ng/mL. The comparison showed that the sensitivity and detection limit of ic-TRFIA were superior to dc-TRFIA. The cross reaction (CR) tests showed that the CR with other oxyfluorfen structure analogues was less than 0.02%, except that there was a certain CR with the benzofluorfen (CR=11.58) and the bifenox (CR=8.23%). The average recoveries of ic-TRFIA were 74.6-108.3%, and the RSDs were between 2.1% and 10.9%, in the addition recovery test with five substrates. The results of the correlation test with the real samples of GC-ECD showed that they were highly correlated (y = 0.975x - 0.4446, R² = 0.9901), which proved that the TRFIA method established in this study had high reliability and accuracy and could be used in environment and agricultural products for rapid detection of oxyfluorfen residues.